THE RELATIONSHIP BETWEEN SPIRITUALITY AND QUALITY OF LIFE OF PATIENTS WITH CORONARY HEART DISEASE - Siregar, Rinco; Sinaga, Taruli Rohana; Simamora, Martalena; Simaremare, Dedi Santina (Jurnal Ilmiah Keperawatan, 2025)
Background: Patients with Coronary Heart Disease (CHD) tend to have a low Quality of Life Purpose: This study aims to identify the relationship between spirituality and the QoL of Patients with CHD. Methods: Descriptive correlational statistics with a cross-sectional design involving inpatients of CHD at the Adventist General Hospital, Medan. There were 89 patients who were selected using a purposive sampling technique. This study used the Daily Spiritual Experience Scale (DSES) and Quality of Life Index (QLI). Spearman Rank Correlation was used to analyze the relationship between the two variables. Results: The results of this study showed that 56.9% of CHD patients had low spirituality, and 52.8% had poor QoL. There is a significant relationship between spirituality and the QoL of CHD patients (r = -0.533; P = 0.001 <0.05). Conclusion: CHD patients with low spirituality have poor QoL. It is very important to provide interventions to improve the spirituality of patients with CHD which can ultimately improve their (QoL), which affects the recovery process. Several QoL. literatures note that the need for spirituality plays an important role in recovery in chronic patients.